2009
DOI: 10.1007/s12665-009-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry of abandoned Pb sulphide mines: the mining district of La Carolina (southern Spain)

Abstract: The impact of past mining activities on the quality of groundwater and surface water has been investigated in the mining district of La Carolina (southern Spain, province of Jaén), a region characterised by the presence of mineralisations of Pb-Ag, Cu and Fe sulphides and Ba sulphates. The chemistry of waters from flooded galleries, shafts and drainage adits has been compared with that of surface waters in the same area. Generally, waters present neutral pH, since carbonates neutralise the acidity produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is not possible to identify clear links between the degree of groundwater transformation caused by mining activity and concentrations of these elements. Elevated concentrations of iron manganese, nickel, arsenic, and other metals in both groundwater and surface water in the areas of Zn-Pb ore mining are reported in numerous studies (e.g., Cidu et al 2001 ; Aykol et al 2003 ; Sainz et al 2004 ; Lee et al 2005 ; Hidalgo et al 2010 ; Sracek et al 2012 ; Bauerek et al 2013 ).
Fig.
…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is not possible to identify clear links between the degree of groundwater transformation caused by mining activity and concentrations of these elements. Elevated concentrations of iron manganese, nickel, arsenic, and other metals in both groundwater and surface water in the areas of Zn-Pb ore mining are reported in numerous studies (e.g., Cidu et al 2001 ; Aykol et al 2003 ; Sainz et al 2004 ; Lee et al 2005 ; Hidalgo et al 2010 ; Sracek et al 2012 ; Bauerek et al 2013 ).
Fig.
…”
Section: Resultsmentioning
confidence: 95%
“…It could be observed that TDS values significantly increased to a few or several grams per liter, while the hydro-chemical type had changed from Ca-Mg-HCO 3 to Ca-Mg-SO 4 and Mg-Ca-SO 4 to Mg-SO 4 . It is a typical phenomenon, commonly occurring in such conditions (Hermann and Neumann-Mahlkau 1985 ; Lee et al 2001 ; Cidu et al 2007 ; Hidalgo et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both human activity and the wind are important contributors to the transport of the metals on suspended particles originating in soil and dust, from open mining pits and/or mine tailings, further away from the mining area (18). Climate conditions also, play a role in the transfer of metals from the deposits zone in the mining areas to the soil in the surroundings, as does the carbonate content of the geologic substrate in the deposits zone, which can influence the acid pH created by the sulfide oxidation processes, thus influencing the mobilization of metals (2,19). Other elements that might affect the metal contamination extent into the residential areas near the mining sites, are the geochemical particularities and the degree of tailings mineralization (20).…”
Section: Discussionmentioning
confidence: 99%
“…These brackish waters gave rise to the formation of precipitates and salt crusts on the surrounding soils, mainly constituted by Ca-Na sulfates and carbonates, together with Na arsenates [36]. Downstream, the water (Ch-3 and Ch-6) was predominantly of the Ca bicarbonate type, with low mineralisation, similar to that of other channels in this mining district [9,57,58]. However, the water in the headwater reach of the creek (Ch-1, Figure 6) was of the Na bicarbonate type, clearly reflecting the mixing between weakly mineralised natural water and the leachates from the smelter.…”
Section: Hydrochemistrymentioning
confidence: 99%